Buccal Resveratrol Delivery System as a Potential New Concept for the Periodontitis Treatment - Magdalena Paczkowska-Walendowska; Jakub Dvořák; Natalia Rosiak; Ewa Tykarska; Emilia Szymańska; Katarzyna Winnicka; Marek A. Ruchała; Judyta Cielecka-Piontek (Pharmaceutics, 2021)
The health benefits of resveratrol have been proven to inhibit the development of numerous diseases. A frequent limitation in its use is a low bioavailability stemming from a poor solubility and fast enterohepatic metabolism. Thus, the aim of the research was to investigate the possibility to formulate mucoadhesive cyclodextrin- and xanthan gum-based buccal tablets in order to increase the solubility of resveratrol and to eliminate bypass enterohepatic metabolism. Systems of resveratrol with α-cyclodextrin (α-CD), β-cyclodextrin (β-CD), γ-cyclodextrin (γ-CD) and 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) prepared by the dry mixing method (ratio 1:1) were selected for the of tablets where xanthan gum was used as a mucoadhesive agent. They were identified on the basis of PXRD, FT-IR analysis. Tablets F1 (with α-CD), F2 (with β-CD) and F3 (with γ-CD) were characterized by the highest compactibility as well as by favorable mucoadhesive properties. Resveratrol release from these tablets was delayed and controlled by diffusion. The tablets prepared in the course of this study appear to constitute promising resveratrol delivery systems and are recommended to increase the effectiveness of the treatment in many diseases, particularly periodontitis.